After Warnock: The Effects of Perverse Incentives in Policies in England for Students With Special Educational Needs - Daniels, Harry; Thompson, Ian; Tawell, Alice (Frontiers in Education, 2019)
The 1978 Warnock Report made the case in the United Kingdom for a number of actions that, it was argued, would make the integration and support of young people with Special Educational Needs more effective. In the aftermath of this wave of policy development, a nascent tension between policies designed to achieve excellence and those seeking to achieve inclusive practice emerged. Whilst the devolved parliaments in Scotland and Wales have continued to try to give priority to inclusion in education, in recent years these tensions in England have intensified and there is growing concern about the ways in which schools are managing the contradictions between these two policy streams. There is widespread public and political unrest about the variety of ways in which young people with special educational needs, who may be seen as a threat to a school attainment profiles, are being excised from the system either through formal exclusion or other, more clandestine, means. This paper charts this move from attempts to meet need with provision as outlined by Warnock to the current situation where the motives which drive the formulation of provision are driven by what are ultimately economic objects. We argue that policy changes in England in particular have resulted in perverse incentives for schools to not meet the needs of special educational needs students and which can result in their exclusion from school. These acts of exclusion in England are then compared to educational policies of segregation in Northern Ireland and then exemplified with data. We illustrate the impact of perverse incentives on practices of inclusion and exclusion through an analysis of interview data of key stakeholders gathered in a recent study of practices of school exclusion in England.